Overexpression of UCP1 in tobacco induces mitochondrial biogenesis and amplifies a broad stress response - Barreto, Pedro; Okura, Vagner Katsumi; Pena Neshich, Izabella Agostinho; Maia, Ivan de Godoy [UNESP]; Arruda, Paulo (Biomed Central Ltd., 2014)
Background: Uncoupling protein one (UCP1) is a mitochondrial inner membrane protein capable of uncoupling the electrochemical gradient from adenosine-5'-triphosphate (ATP) synthesis, dissipating energy as heat. UCP1 plays a central role in nonshivering thermogenesis in the brown adipose tissue (BAT) of hibernating animals and small rodents. A UCP1 ortholog also occurs in plants, and aside from its role in uncoupling respiration from ATP synthesis, thereby wasting energy, it plays a beneficial role in the plant response to several abiotic stresses, possibly by decreasing the production of reactive oxygen species (ROS) and regulating cellular redox homeostasis. However, the molecular mechanisms by which UCP1 is associated with stress tolerance remain unknown.Results: Here, we report that the overexpression of UCP1 increases mitochondrial biogenesis, increases the uncoupled respiration of isolated mitochondria, and decreases cellular ATP concentration. We observed that the overexpression of UCP1 alters mitochondrial bioenergetics and modulates mitochondrial-nuclear communication, inducing the upregulation of hundreds of nuclear-and mitochondrial-encoded mitochondrial proteins. Electron microscopy analysis showed that these metabolic changes were associated with alterations in mitochondrial number, area and morphology. Surprisingly, UCP1 overexpression also induces the upregulation of hundreds of stress-responsive genes, including some involved in the antioxidant defense system, such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione-S-transferase (GST). As a consequence of the increased UCP1 activity and increased expression of oxidative stress-responsive genes, the UCP1-overexpressing plants showed reduced ROS accumulation. These beneficial metabolic effects may be responsible for the better performance of UCP1-overexpressing lines in low pH, high salt, high osmolarity, low temperature, and oxidative stress conditions.Conclusions: Overexpression of UCP1 in the mitochondrial inner membrane induced increased uncoupling respiration, decreased ROS accumulation under abiotic stresses, and diminished cellular ATP content. These events may have triggered the expression of mitochondrial and stress-responsive genes in a coordinated manner. Because these metabolic alterations did not impair plant growth and development, UCP1 overexpression can potentially be used to create crops better adapted to abiotic stress conditions.
Keywords: UCP1; Mitochondria; Oxidative stress; Biogenesis; Plant; Stress response